2017
DOI: 10.1017/s0003055416000745
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst or Crown: Does Naturalization Promote the Long-Term Social Integration of Immigrants?

Abstract: We study the impact of naturalization on the long-term social integration of immigrants into the host country society. Despite ongoing debates about citizenship policy, we lack reliable evidence that isolates the causal effect of naturalization from the non-random selection into naturalization. We exploit the quasi-random assignment of citizenship in Swiss municipalities that used referendums to decide on naturalization applications of immigrants. Comparing otherwise similar immigrants who narrowly won or narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
101
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 49 publications
8
101
0
2
Order By: Relevance
“…Nevertheless, to our knowledge, there is currently no empirical evidence of the effectiveness of these programs. Moreover, these novel efforts should not supplant public policy efforts to integrate migrants and refugees, as there is evidence of the causal effect of naturalization on increased social integration, particularly for the most marginalized migrants [66]. …”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Nevertheless, to our knowledge, there is currently no empirical evidence of the effectiveness of these programs. Moreover, these novel efforts should not supplant public policy efforts to integrate migrants and refugees, as there is evidence of the causal effect of naturalization on increased social integration, particularly for the most marginalized migrants [66]. …”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Most recently, Hainmueller et al . () have used local referendums on citizenship applications in Switzerland in an RDD design to analyse whether narrowly winning the citizenship referendum improves the political and social integration of immigrants.…”
mentioning
confidence: 99%
“…concluded that citizenship fosters immigrants' socio-political inclusion and political engagement. Hainmueller et al (2017) found in Switzerland that naturalization also promoted immigrants' long-term integration. The design of Hainmueller et al (2017Hainmueller et al ( , see also 2015 was unique in its focus on close naturalization referendums, in which the naturalization decision was as good as random, enabling them to study the causal relationship between citizenship and integration outcomes.…”
mentioning
confidence: 98%
“…Hainmueller et al (2017) found in Switzerland that naturalization also promoted immigrants' long-term integration. The design of Hainmueller et al (2017Hainmueller et al ( , see also 2015 was unique in its focus on close naturalization referendums, in which the naturalization decision was as good as random, enabling them to study the causal relationship between citizenship and integration outcomes. There is also valuable longitudinal evidence from Germany (Fick, 2016;Maehler et al, 2019) supporting the idea that citizenship acquisition promotes identification with receiving society and might also support the compatibility of ethnic and civic national identities.…”
mentioning
confidence: 98%